Molecular characterization of human thyroid hormone receptor β isoform 4. (2nd January 2016) - Moriyama, Kenji; Yamamoto, Hiroyuki; Futawaka, Kumi; Atake, Asami; Kasahara, Masato; Tagami, Tetsuya
Abstract: Thyroid hormone exerts a pleiotropic effect on development, differentiation, and metabolism through thyroid hormone receptor (TR). A novel thyroid hormone receptor β isoform (TRβ4) was cloned using PCR from a human pituitary cDNA library as a template. We report here the characterization of TRβ4 from a molecular basis. Temporal expression of TRβ4 during the fetal period is abundant in the brain and kidney, comparable with the adult pattern. Western blot analysis revealed that TRs are ubiquitination labile proteins, while TRβ1 is potentially stable. TRβ1, peroxisome proliferator-activated receptors (PPAR), and vitamin D receptor (VDR), which belong to class II transcription factors that function via the formation of heterodimeric complexes with retinoid X receptor (RXR), were suppressed by TRβ4 in a dose-dependent manner. Thus, TRβ4 exhibits ligand-independent transcriptional silencing, possibly as a substitute for dimerized RXR. In this study, TRβ1 and TRβ4 transcripts were detected in several cell lines. Quantitative RT-PCR assay showed that the expression of TRβ4 in human embryonic carcinoma cells of the testis was suppressed by sex hormone in a reciprocal manner to TRβ1. In contrast, TRβ4 was expressed under a high dose of triiodothyronine (T3) in a reciprocal manner to TRβ1. Finally, in transiently transfected NIH-3T3 cells, green fluorescence protein (GFP)-tagged TRβ4 was mostly nuclear in both the absence and the presence of T3. By mutating defined regions of both TRβs, we found that both TRβ1 and TRβ4 had altered nuclear/cytoplasmic distribution as compared with wild-type, and different to T3 and the nuclear receptor corepressor (NCoR). Thus, site-specific DNA binding is not essential for maintaining TRβs within the nucleus.